2011
DOI: 10.3390/w3020650
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Quality Status of Rivers for the Water Framework Directive: A Case Study of Toxic Metals in North West England

Abstract: This paper provides data from two years of monitoring of the chemical quality of rivers and streams in North West England from the clean headwaters to polluted rivers just above the tidal reach and covers 26 sites including the Ribble, Wyre and the tributary rivers of the Calder and Douglas. Across the basins that include areas of rural, urban and industrial typologies, data is presented for three of the priority substances in the Water Framework Directive i.e., nickel (Ni), cadmium (Cd), and lead (Pb). Averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The current risk associated with diffuse and point source inputs of the priority substances associated with the Water Framework Directive is low. Rowland et al (2010c) found no annual average concentrations of dissolved Pb, Cd, Ni and Hg in the Ribble and Wyre catchment above the regulatory Environmental Quality Standard values, and neither were there any values exceeding the defined maximum allowable concentrations. Comparing more recent data for the Ribble and Wyre (Neal et al, 2011a) with earlier studies of the eastern UK rivers (Neal and Robson, 2000;Neal and Davies, 2003) indicates that pollutant concentrations have generally declined over the past 20 years when considering similar catchment typologies.…”
Section: 6mentioning
confidence: 99%
“…The current risk associated with diffuse and point source inputs of the priority substances associated with the Water Framework Directive is low. Rowland et al (2010c) found no annual average concentrations of dissolved Pb, Cd, Ni and Hg in the Ribble and Wyre catchment above the regulatory Environmental Quality Standard values, and neither were there any values exceeding the defined maximum allowable concentrations. Comparing more recent data for the Ribble and Wyre (Neal et al, 2011a) with earlier studies of the eastern UK rivers (Neal and Robson, 2000;Neal and Davies, 2003) indicates that pollutant concentrations have generally declined over the past 20 years when considering similar catchment typologies.…”
Section: 6mentioning
confidence: 99%
“…These are generally released into the environment from anthropogenic sources (Álvarez-Ayuso et al, 2012;Förstner, 2004;Prabakaran et al, 2019;Rennert et al, 2017). Floodplains located in urban catchment areas are contaminated from sources including wastewater/sewage treatment plants, factories using alloys, metal mining, landfills, and road surface runoff from tyre and brake emissions into the river (Hurley et al, 2017;Rowland et al, 2011;Stuart and Lapworth, 2011). Soils have the ability to retain Much of the understanding about the influence of flooding on PTE mobility in floodplains has come from laboratory experiments undertaken in mesocosms.…”
Section: Introductionmentioning
confidence: 99%
“…The UKTAG established an environmental quality standard (EQS) for dissolved Pb in surface water of 7.2 ppb (Rowland et al 2011). Generally, the ionic form of Pb (Pb 2+ ) is considered most toxic.…”
Section: Introductionmentioning
confidence: 99%